Protective effect of probiotic (Lactobacillus casei) against Escherichia coli causing diarrhea - J.Turki, Dhuhaa Kh.Kareem, Ali; M.Alsheikly, Abeer ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Based on the significant impact of L. casei against E. coli obtained from diarrheal case in several Baghdadi hospitals (Yarmouk and Mahmoudia), this study was conducted. Every sample that was grown on MacConkey agar, Eosine Methylene Blue, and Blood agar, as well as E. coli, was identify using Gram stain and biochemical testing. Forty-five isolates of the fifty diarrheal samples had positive E. coli results. Sensitivity tests were performed on the four E. Coli isolates that were obtained and came back positive Lactobacillus casei isolates were isolated and cultur in Man Rogosa Sharpe broth at 37°C for 24 hours, followed by a 24-hour incubation under CO2 (5–10%) and a reculture on MRS agar. The isolates were tested against E. coli using the agar well diffusion assay, and the diameter of the halo zone surrounding bacterial growths was measured. DOI: https://doi.org/10.54633/2333-024-056-006